2021
DOI: 10.1371/journal.pone.0248042
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex Loop-Mediated Isothermal Amplification (LAMP) assay for on-site diagnosis of SARS CoV-2

Abstract: A newly identified coronavirus, designated as severe acute respiratory syndrome coronavirus 2 (SARS CoV-2), has spread rapidly from its epicenter in China to more than 150 countries across six continents. In this study, we have designed three reverse-transcription loop-mediated isothermal amplification (RT-LAMP) primer sets to detect the RNA-dependent RNA polymerase (RdRP), Envelope (E) and Nucleocapsid protein (N) genes of SARS CoV-2. For one tube reaction, the detection limits for five combination SARS CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 27 publications
4
55
0
1
Order By: Relevance
“…With the current conditions, none of the targets were capable of detecting 50 copies. The results obtained are in the same range of other previously published RT-LAMP studies, such as the one from Jang et al, which reached 10 1 -10 2 copies/µL targeting RdRp, E, and N, or that of Mautner et al, who reported limited detection of 10 2 copies/µL [23,32]. Minor differences among assays may be explained due to the usage of different chemicals, primer concentration, and/or amplification temperature and time.…”
Section: Dynamic Rangesupporting
confidence: 87%
See 2 more Smart Citations
“…With the current conditions, none of the targets were capable of detecting 50 copies. The results obtained are in the same range of other previously published RT-LAMP studies, such as the one from Jang et al, which reached 10 1 -10 2 copies/µL targeting RdRp, E, and N, or that of Mautner et al, who reported limited detection of 10 2 copies/µL [23,32]. Minor differences among assays may be explained due to the usage of different chemicals, primer concentration, and/or amplification temperature and time.…”
Section: Dynamic Rangesupporting
confidence: 87%
“…In this regard, national regulations of different countries highlight the need for multiplex detection of positive result. Jang et al also reported higher sensitivity targeting the N gene in their multiplex RT-LAMP assay implementing strand-displacement probes [32]. Some of the discrepancies between the RT-LAMP and the reference RT-qPCR assays may be explained by the difference in template analyzed (3 vs. 10 µL).…”
Section: Clinical Samples Analyzedmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this goal, several studies have tackled this challenge and these efforts have yielded several diagnostic kits. Many approaches have been proposed to detect SARS-CoV-2 virus in nasopharyngeal fluids such as multiplex RT-PCR [2,3], CRISPR/Cas12 [4,5], and CRISPR-Cas3 [6], lateral flow immunoassay [7], paper-based biomolecular sensors [8], SHERLOCK testing in one pot [9], DNA aptamer [10], loop-mediated isothermal amplification (LAMP) [11], etc. Each of these methods has its own strong and weak points in terms of sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be performed without the use of thermocyclers and tends to be faster than RT-PCR. Several LAMP assays for SARS-CoV-2 detection have been developed [ 4 ], and a limited number of them have been evaluated using clinical samples with promising initial results [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%